Identification of signaling pathways modifying human dopaminergic neuron development using a pluripotent stem cell-based high-throughput screening automated system: purinergic pathways as a proof-of-principle - Claire Boissart; Marie Lasbareilles; Marie Lasbareilles; Marie Lasbareilles; Johana Tournois; Laure Chatrousse; Thifaine Poullion; Alexandra Benchoua; Alexandra Benchoua (Frontiers Media S.A., 2023)
Introduction: Alteration in the development, maturation, and projection of dopaminergic neurons has been proposed to be associated with several neurological and psychiatric disorders. Therefore, understanding the signals modulating the genesis of human dopaminergic neurons is crucial to elucidate disease etiology and develop effective countermeasures.Methods: In this study, we developed a screening model using human pluripotent stem cells to identify the modulators of dopaminergic neuron genesis. We set up a differentiation protocol to obtained floorplate midbrain progenitors competent to produce dopaminergic neurons and seeded them in a 384-well screening plate in a fully automated manner.Results and Discussion: These progenitors were treated with a collection of small molecules to identify the compounds increasing dopaminergic neuron production. As a proof-of-principle, we screened a library of compounds targeting purine- and adenosine-dependent pathways and identified an adenosine receptor 3 agonist as a candidate molecule to increase dopaminergic neuron production under physiological conditions and in cells invalidated for the HPRT1 gene. This screening model can provide important insights into the etiology of various diseases affecting the dopaminergic circuit development and plasticity and be used to identify therapeutic molecules for these diseases.